Smoking Cessation Intervention Trial Outcomes for Sexual and Gender Minority Young Adults - Vogel, Erin A. (Health Psychol, 2018)
OBJECTIVE: Sexual and gender minority (SGM) individuals are more likely to smoke than non-SGM individuals. It is unclear whether smoking cessation interventions for young adults are effective in the SGM population. The purpose of this study was to compare smoking cessation, other health risk behaviors, and intervention usability between SGM and non-SGM young adult smokers participating in a digital smoking cessation intervention trial. METHODS: Young adult smokers (N = 500; 135 SGM) were assigned to a 90-day Facebook smoking cessation intervention (treatment) or referred to Smokefree.gov (control). Intervention participants were assigned to private Facebook groups tailored to their readiness to quit smoking. Participants reported their smoking status and other health risk behaviors at baseline, 3, 6, and 12 months. Usability of the intervention (i.e., perceptions of the intervention and treatment engagement) was assessed in the intervention group at 3 months. RESULTS: Smoking cessation and intervention usability did not significantly differ between SGM participants and non-SGM participants. A greater proportion of SGM participants were at high risk for physical inactivity over the 12-month follow-up period (OR = 1.55, p = .005). CONCLUSION: SGM and non-SGM young adult smokers did not differ in their smoking cessation rates, perceptions of, or engagement in a digital intervention. Health risk behavior patterns were mostly similar; however, the disparity in physical activity between SGM and non-SGM smokers widened over time. Tailored interventions for SGM young adult smokers could increase focus on SGM experiences that can underlie multiple health risk behaviors, such as discrimination and the normativity of smoking.